Physiological changes in unripe banana fruits during chemodiagnosis of latent infection of Colletotrichum musae by paraquat - and K. RAJAPPAN, S. RAJESWARI, A. PALANISWAMI (Indian Phytopathology, 2002)
Paraquat (Gramaxone) induced physiological changes in unripe banana fruits, which in turn facilitated the early detection of latent infection of C. musae within 5 days compared with 8 days in the untreated control. Paraquat at 100-500 p.p.m. reduced the starch and phenol content in unripe banana fruits with a concomitant increase in sugar at 5 days after treatment. Starch content of pulp and peel from 500 p.p.m. paraquat-treated fruits at 5 days after treatment was 2.51 and 1.14% respectively, compared with 3.64% in peel and 9.00% in pulp from the untreated control. A similar trend was observed with respect to phenol which recorded 0.80 mg/g in peel and 0.25 mg/g pulp in 500 p.p.m. of paraquat-treated fruits 5 days after treatment compared with 1.26 and 0.44 mg/g respectively, in peel and pulp of the untreated control. With regard to sugars, the content increased from 2.65 to 6.20% in peel and 3.35 to 8.75% in pulp from 500 p.p.m. of paraquat-treated fruits while in the control the content increased from 1.80 to 4.40% in peel and 3.15 to 5.49% in pulp, respectively. The effect of paraquat treatment was more pronounced at 500 p.p.m. compared with the control and the lower concentrations.